Prosody Analysis of Acoustic Language Phonetic Research on Minang Kabau - Mutia Irhamni; Tengku Syarfina (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
Prosody in the Minang Kabau language in this study was studied with 5 words, to find formants, frequency, intensity. They are /saruang/, /urang, /goreang/, /putiah/, /karajo/. The results show that the dominance of the predominant vowel is very high in these words. The words were also studied with frequency, intonation and duration to find the sound contour statistically. The results of the study are displayed through diagrams tables and explanations to understand the characteristics of sound, improve language learning ability. The earlier formant diagram shows the position of the tongue, with F3 representing the rear position, F2 representing the middle, and F1 representing the peak of the vowel (Predominant). The research method is the use of the Praat instrument to discuss the recorded and analyzed sounds. Minang Kabau, also known as Minang, has some phonetic peculiarities that distinguish it from other languages. Its broad vowel system, which comprises seven or eight vowels depending on dialectal variety, is one unique feature. Among these vowels are five monophthongs (/i, e, a, o, u/) and two or three diphthongs (/ai, au/, and maybe /oi/). Apart from this, there are vowel length distinctions in Minang Kabau, with both long and short vowels conceivable. In addition, the language has a consonant phoneme inventory that includes voiceless stops (/p, t, k/) and voiced stops (/b, d, g/), as well as a variety of other consonants.